2017
DOI: 10.3892/ijo.2017.3976
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of IGF1R and ER enhances response to trastuzumab in HER2 positive breast cancer cells

Abstract: Although HER2 targeted therapies have improved prognosis for HER2 positive breast cancer, HER2 positive cancers which co-express ER have poorer response rates to standard HER2 targeted therapies, combined with chemotherapy, than HER2 positive/ER negative breast cancer. Administration of hormone therapy concurrently with chemotherapy and HER2 targeted therapy is generally not recommended. Using publically available gene expression datasets we found that high expression of IGF1R is associated with shorter diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…In this line, we found that NRP1 is also upregulated in HER2-addicted breast cancer cells subjected to targeted therapy. NRP1 is pivotal in this system to induce IGF1R tyrosine kinase expression and activity, a mechanism known to mediate resistance to HER2-targeted inhibitors (45). Similar to what we observed for melanoma, NRP1 upregulation is frequently seen in breast cancer samples upon treatment with HER2 inhibitors.…”
Section: Discussionsupporting
confidence: 81%
“…In this line, we found that NRP1 is also upregulated in HER2-addicted breast cancer cells subjected to targeted therapy. NRP1 is pivotal in this system to induce IGF1R tyrosine kinase expression and activity, a mechanism known to mediate resistance to HER2-targeted inhibitors (45). Similar to what we observed for melanoma, NRP1 upregulation is frequently seen in breast cancer samples upon treatment with HER2 inhibitors.…”
Section: Discussionsupporting
confidence: 81%
“…In order to exploit the anti‐tumourigenic responses to INSR/IGF1R inhibition seen in preclinical experiments, current investigations are concentrating on combinatorial studies using IGF inhibitors. Combination with other RTK TKIs is used as a means of reducing the emergence of resistance or in addition to either standard chemotherapeutic agents or radiotherapy utilizing their properties as chemo‐ and radiosensitizers, respectively (McDermott et al ., ; Schaffrath et al ., ). Given the importance of the PI3K/AKT pathway in TGCT, simultaneous multiple targeting of this pathway may be effective in TGCT patients by combining IGF1R inhibition with other inhibitors of this pathway.…”
Section: Therapeutic Targeting Of the Igf System In Cancermentioning
confidence: 99%
“…It was found that a combined treatment with selective ER modulator and IGF1R inhibitor was significantly more effective than using a single-agent treatment on different ER + and HER2 +/− cell lines with variable IGF1R intensity. This effect was due to the induction of cell-cycle arrest (11).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of IGF1R in BC cells was found to be due to an increase in IGF1 that is regulated by estradiol through synergistically stimulating cancer cell proliferation and suppressing several tumor-suppressor genes (11). Whereas it has been shown that there is a cross talk between estrogen receptor positivity (ER + ) and IGF1R expression owing to up-regulation of IGF1R transcription through activating ER complexes (12).…”
mentioning
confidence: 99%